Developing the Administration of Egyptian New Cities: A Comparative Study - Elbagoury, Ayman; George, Roshdy (The Arab Journal of Administration, 2022)
This study aimed at developing the administration of the Egyptian new cities, by presenting and analyzing the British experience. This study is divided into four parts, by using the comparative methodology; the first part explained the history and the developments of the Egyptian and the British new cities. The second part discussed the main characteristics of managing new cities in both experiences. The third part focused on the relationship between the new cities and the local authorities. The fourth part discussed the main trials that have been conducted to develop the administration of the new cities in both cases. The study suggested a four-dimensional vision for developing the administration of the new cities in Egypt; the first dimension includes the aspects of developing legal framework governing the new cities in Egypt, the second dimension deals with the organizational aspects, the third dimension discusses the role of community participation in developing and reforming the administration of the Egyptian new cities, and the fourth dimension relates to the financial aspects of establishing new cities in Egypt. The study recommends the necessity of establishing a commission for new cities in Egypt in order to coordinate the relationships between New Urban Community Authority and branches of central ministries within which they operate.